Analisis Faktor Yang Mempengaruhi Likuiditas Pada Perusahaan Asusransi yang Terdaftar di Bursa Efek Indonesia - Jusmarni Jusmarni; Asepma Hygi Prihastuti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This study aims to examine the effect of Debt Ratio, Cash Flow Ratio, Capital Turnover Ratio on liquidity in general insurance companies listed on the Indonesia Stock Exchange 2017-2019. In recent years, the financial industry, especially the Indonesian insurance sector, has been faced with a number of problems that have caused insurance companies to experience problems in terms of liquidity and insolvency. Based on purposive sampling, the number of samples used in the study were 14 companies from 42 observation companies. Hypothesis testing using multiple linear regression. The results showed that the Debt Ratio and Capital Turnover Ratio had no effect on the company's liquidity. While the Cash Flow Ratio has an influence on the Liquidity of Insurance Companies listed on the Indonesia Stock Exchange